2021
DOI: 10.1073/pnas.2010210118
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear to cytoplasmic ratio directly regulates zygotic transcription in Drosophila through multiple modalities

Abstract: Early embryos must rapidly generate large numbers of cells to form an organism. Many species accomplish this through a series of rapid, reductive, and transcriptionally silent cleavage divisions. Previous work has demonstrated that the number of divisions before both cell cycle elongation and zygotic genome activation (ZGA) is regulated by the ratio of nuclear content to cytoplasm (N/C). To understand how the N/C ratio affects the timing of ZGA, we directly assayed the behavior of several previously identified… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…An important and recently debated ( Strong et al, 2020 ; Syed et al, 2021 ) example of such a potentially autonomous developmental timing mechanism that can run independently of the cell cycle progression is the program that triggers cellularization during mid-blastula transition (MBT) in embryogenesis ( Figure 3A ). Organismal development unfolds on a tight schedule and in specific sequences that are unlikely to be reproduced by stochasticity.…”
Section: The Emerging Concept Of Autonomous Clocks and Their Mechanisms At Different Scales And Complexitiesmentioning
confidence: 99%
“…An important and recently debated ( Strong et al, 2020 ; Syed et al, 2021 ) example of such a potentially autonomous developmental timing mechanism that can run independently of the cell cycle progression is the program that triggers cellularization during mid-blastula transition (MBT) in embryogenesis ( Figure 3A ). Organismal development unfolds on a tight schedule and in specific sequences that are unlikely to be reproduced by stochasticity.…”
Section: The Emerging Concept Of Autonomous Clocks and Their Mechanisms At Different Scales And Complexitiesmentioning
confidence: 99%
“…To define the A-P position represented by each uniformly expressed Bcd-LEXY construct, we measured the transcriptional activity for four gap genes ( gt , hb , Kr , and kni ) (see STAR Methods ). We used previously published MS2 reporters for each gap gene in which multi-enhancer regulatory sequences (~20 kb upstream sequences for hb and kni , a 10 kb upstream sequence for gt , and the 4 kb CD1 + CD2 enhancer regions for Kr ) drive expression of 24xMS2 stem loops followed by the yellow gene ( Bothma et al, 2015 ; El-Sherif and Levine, 2016 ; Syed et al, 2021 ). We confirmed that each reporter closely matched the expected endogenous patterns of gap gene expression in embryos with intact A-P patterning ( Figures S2B and S2C ).…”
Section: Resultsmentioning
confidence: 99%
“…How do the anterior expression dynamics of gt compare with those of hb ? We examined the gt MS2 reporter ( Syed et al, 2021 ) under similar light-to-dark and dark-to-light illumination shifts in NC14 ( Figures 4F – 4H and S6B ). As in the case of hb , we found that optogenetic Bcd perturbations were rapidly transmitted to transcription of gt MS2, with response times of 5.9 ± 1.6 and 9 ± 2.7 min depending on the illumination sequence ( Figures 4G and 4H ; Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A rapid initial response followed by delayed progression towards a final state is suggestive of positive autoregulation 27 , for example if gt transcription were positively influenced by the past history of gap gene (gt or hb) expression. Indeed, positive feedback on gt transcription by Gt protein was recently reported 26 .…”
Section: Anterior Patterns Of Hb and Gt Respond Rapidly To Changes In Nuclear Bcd Concentrationsmentioning
confidence: 96%
“…How do the anterior expression dynamics of gt compare to those of hb? We examined a gt MS2 reporter 26 under similar light-to-dark and dark-to-light illumination shifts in NC14 (Figure 4f-h; Figure S4b). As in the case of hb, we found that optogenetic Bcd perturbations were rapidly transmitted to gt expression, with response times of 5.9 ± 1.6 min and 9 ± 2.7 min S2).…”
Section: Anterior Patterns Of Hb and Gt Respond Rapidly To Changes In Nuclear Bcd Concentrationsmentioning
confidence: 99%